2021
DOI: 10.1038/s41598-021-90253-z
|View full text |Cite
|
Sign up to set email alerts
|

GRK2 contributes to glucose mediated calcium responses and insulin secretion in pancreatic islet cells

Abstract: Diabetes is a metabolic syndrome rooted in impaired insulin and/or glucagon secretory responses within the pancreatic islets of Langerhans (islets). Insulin secretion is primarily regulated by two key factors: glucose-mediated ATP production and G-protein coupled receptors (GPCRs) signaling. GPCR kinase 2 (GRK2), a key regulator of GPCRs, is reported to be downregulated in the pancreas of spontaneously obesogenic and diabetogenic mice (ob/ob). Moreover, recent studies have shown that GRK2 non-canonically local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Moreover, MIN6 cells with β-arrestin2 knockdown and mice with β-arrestin2 KO in β-cells have impaired glucose-stimulated insulin secretion (GSIS) from inactivation of calmodulin kinase II (CAMKII) ( 27 ). This is similar to that seen in mice with pancreatic deletion of GRK2, where glucose intolerance and diminished insulin secretion is observed ( 28 ). Since β-arrestin function is often preceded by GPCR phosphorylation by GRKs, these non-GPCR pathways suggest alternative modes to β-arrestin activation.…”
supporting
confidence: 85%
“…Moreover, MIN6 cells with β-arrestin2 knockdown and mice with β-arrestin2 KO in β-cells have impaired glucose-stimulated insulin secretion (GSIS) from inactivation of calmodulin kinase II (CAMKII) ( 27 ). This is similar to that seen in mice with pancreatic deletion of GRK2, where glucose intolerance and diminished insulin secretion is observed ( 28 ). Since β-arrestin function is often preceded by GPCR phosphorylation by GRKs, these non-GPCR pathways suggest alternative modes to β-arrestin activation.…”
supporting
confidence: 85%
“…Interestingly, a subsequent study reported that silencing GRK2 in MIN6 cells led to diminution of GSIS that was recovered by PTX treatment ( Snyder et al, 2021 ). This suggested that loss of GRK2-mediated regulation/phosphorylation of G i -coupled receptors allowed these receptors to influence β -cell secretory tone by maintaining G i signaling and inhibiting GSIS.…”
Section: G Protein–coupled Receptor Kinase Function In the ...mentioning
confidence: 99%
“…Furthermore, in mice with pancreatic-specific GRK2 knockout, a similar effect was seen, where insulin secretion was reduced and cardiac function attenuated, with both exacerbated by a high-fat diet. Essentially, GRK2 had a positive effect on insulin secretion by keeping G i signaling in check ( Snyder et al, 2021 ). This contrasts with previous reports that show GRK2 inhibition as having beneficial outcomes in metabolic parameters, such as glucose tolerance ( Usui et al, 2004 ; Vila-Bedmar et al, 2015 ; Taguchi et al, 2017 ; Cipolletta et al, 2019 ).…”
Section: G Protein–coupled Receptor Kinase Function In the ...mentioning
confidence: 99%
“…Nonetheless, β-adrenergic stimulation revealed increased sensitivity of inotropic and lusitropic tachyphylaxis in the adult heart, suggesting the importance of cardiac GRK2 in protective effects in cardiomyopathy induced by catecholamine toxicity [ 115 ]. Further studies, using pancreatic-specific GRK2 knockout mice revealed a decrease in glucose-mediated insulin secretion linked to decreased calcium influx in pancreatic islets [ 123 ]. Whether this is developmentally linked remains to be further investigated but may be an important contributor to diabetes disease progression.…”
Section: Grk2 and β-Arrestin Signalingmentioning
confidence: 99%
“…Overall preventing GRK2 upregulation in the heart appears to be a viable strategy to treat HF. Notably, recent studies have shown that whole pancreas GRK2 knockdown leads to decreased glucose-mediated insulin secretion, increased weight gain when in a high fat regimen, and decreased cardiac function [ 123 ]. Kidney inhibition of GRK2 has also been reported to negatively impact kidney function and blood pressure [ 136 ].…”
Section: Grk2 and β Arrestin In Diseasesmentioning
confidence: 99%